Navigating the Whistleblowing and Fraud Prevention Literature: A Scopus-Based Bibliometric Exploration - Ratna Marta Dhewi (Jurnal Ilmiah Akuntansi, 2023)
This research undertakes a thorough examination of whistleblowing and fraud prevention literature through a Scopus-based bibliometric analysis. The study identifies influential works, offering thematic insights valuable for academics and practitioners concerned with corporate accountability. The analysis of publication frequency, metrics of citation, and visualization of data covers 12,791 citations from 200 whistleblowing-related articles spanning 1982-2022. The primary keyword, strongly linked to "whistleblowing system," "accounting and fraud," and "company," holds a total link strength of 1,683. Contributions from 285 scholars across 44 publishers in 7 countries, encompassing various languages, are analyzed. Leading publisher Springer Netherlands, with 57 publications and 4,295 citation counts, is highlighted. The most prolific whistleblowing writer was J.P. Keenan from The Institute for Leadership and Global Education, United States. The study employs network visualization tools to outline the centrality features of keyword clusters. Additionally, it provides a summary of positive and negative determinants in predicting whistleblowing and fraud reporting intentions. This marks the first comprehensive review of Scopus-based whistleblowing and fraud prevention literature.